Validation of the Primary Care Patient Measure of Safety (PC PMOS) questionnaire - Giles, Sally J (BMJ Qual Saf, 2019)
BACKGROUND: The Primary Care Patient Measure of Safety (PC PMOS) is designed to capture patient feedback about the contributing factors to patient safety incidents in primary care. It required further reliability and validity testing to produce a robust tool intended to improve safety in practice. METHOD: 490 adult patients in nine primary care practices in Greater Manchester, UK, completed the PC PMOS. Practice staff (n = 81) completed a survey on patient safety culture to assess convergent validity. Confirmatory factor analysis (CFA) assessed the construct validity and internal reliability of the PC PMOS domains and items. A multivariate analysis of variance was conducted to assess discriminant validity, and Spearman correlation was conducted to establish test–retest reliability. RESULTS: Initial CFA results showed data did not fit the model well (a chi-square to df ratio (CMIN/DF) = 5.68; goodness-of-fit index (GFI) = 0.61, CFI = 0.57, SRMR = 0.13 and root mean square error of approximation (RMSEA) = 0.10). On the basis of large modification indices (>10), standardised residuals >± 2.58 and assessment of item content; 22 items were removed. This revised nine-factor model (28 items) was found to fit the data satisfactorily (CMIN/DF = 2.51; GFI = 0.87, CFI = 0.91, SRMR = 0.04 and RMSEA = 0.05). New factors demonstrated good internal reliability with average inter-item correlations ranging from 0.20 to 0.70. The PC PMOS demonstrated good discriminant validity between primary care practices (F = 2.64, df = 72, p < 0.001) and showed some association with practice staff safety score (convergent validity) but failed to reach statistical significance (r = −0.64, k = 9, p = 0.06). CONCLUSION: This study led to a reliable and valid 28-item PC PMOS. It could enhance or complement current data collection methods used in primary care to identify and prevent error.